2005
DOI: 10.1159/000083712
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Metals and Minerals from Phosphate Binders

Abstract: Metals and minerals that depend on renal clearance may accumulate to toxic levels in patients with marginal kidney function. Toxicities of aluminum-based phosphate binders became apparent ∼25 years ago. Nephrologists now recognize cardiovascular calcification may follow use of calcium-based phosphate binders. Five lessons can be learned: (1)safety must not be assumed in absence of data; (2) all evidence for causal linkage of toxicities from therapeutics must be considered, including animal data; (3) clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 146 publications
0
15
0
Order By: Relevance
“…Box plots display 5th, 25th, 50th, 75th, and 95th percentiles. Under the repeated measures mixed effects model, the mean difference in serum phosphorus between the ferric citrate and active control groups over weeks 12,24,36,48, and 52 was 20.0127 mg/dl (95% confidence interval, 20.056 to 0.030 mg/dl). AC, active control; FC, ferric citrate.…”
Section: Discussionmentioning
confidence: 98%
“…Box plots display 5th, 25th, 50th, 75th, and 95th percentiles. Under the repeated measures mixed effects model, the mean difference in serum phosphorus between the ferric citrate and active control groups over weeks 12,24,36,48, and 52 was 20.0127 mg/dl (95% confidence interval, 20.056 to 0.030 mg/dl). AC, active control; FC, ferric citrate.…”
Section: Discussionmentioning
confidence: 98%
“…For all these reasons, new types of noncalcium or aluminum-based agents, sevelamer hydrochloride and lanthanum carbonate, have more recently become available in the US and Europe. Their use is increasing in current practice, and although they are more expensive, the potential decrease in risk of vascular calcification and toxicity advocates for broader adoption [17,18]. However, these products are not yet available in China and other developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that long-term LC treatment is possible provided gastrointestinal events that tend to occur more frequently in the early phase of treatment can be controlled. Another potential safety concern of LC treatment is toxicity in bone, liver, and the central nervous system [11][12][13][14][15]. The long-term safety profile of LC in hemodialysis patients receiving treatment for up to 6 years have been reported and appear to show no evidence of adverse effects on the liver, bone, or the central nervous system [9].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the efficacy and safety of LC administration over 2, 3, and 6 years have consistently reported that LC is well tolerated with no evidence of safety-related issues [7][8][9][10]. Despite this evidence supporting its safety, concerns over the long-term safety of LC persist because some reports have suggested the potential risks of lanthanum (La) deposition and toxicity in the gastrointestinal tract, bone, liver, and central nervous system [11][12][13][14][15]. These safety concerns would appear to be at least partially based on the known toxicities of aluminium (Al)-containing P binders (PBs), which were commonly used between 1970 and 1990.…”
Section: Introductionmentioning
confidence: 99%